The protection of transmission network systems using Discrete Wavelet transforms - Ngaopitakkul, Atthapol; Pothisarn, Chaichan (My University, 2012)
This paper proposes a novel protective relay algorithm to protect transmission systems using Discrete Wavelet Transforms (D WT). Fault conditions are simulated using PSCAD/EMTDC in order to obtain current signals. Various cases based on Thailand electricity transmission systems are carried out to verify the validity of the proposed technique. The maximum coefficients of the positive sequence current obtained from all buses are compared in order to detect the faulty bus on a three-bus transmission network with a loop structure. The first peak time of positive sequence current obtained from the faulty bus is used as input data for travelling wave equation. The coefficient ratio between buses that the fault occurs is calculated so that the proper protective relay sequence can be selected. The result is shown that the proposed algorithm is capable of locating the fault position as well as arranging the protective relay sequence, with satisfactory accu¬racy results, and is suitable for all types of fault that occurs in different sections on the transmission lines. © 2012 ICIC International.
Keywords: Fault; Protective relay sequence; Transmission system; Wavelet transform